Tolerance and Resistance of Pseudomonas aeruginosa Biofilms to Antimicrobial Agents—How P. aeruginosa Can Escape Antibiotics - Ciofu, Oana; Tolker-Nielsen, Tim (Frontiers in Microbiology, 2019)
The ESKAPE pathogen Pseudomonas aeruginosa is recognized as an important cause of chronic infections due to its ability to form biofilms where the bacteria are present in aggregates encased in a self-produced extracellular matrix and are difficult or impossible to eradicate with antibiotic treatment. P. aeruginosa is causing chronic infections in the lungs of patients with cystic fibrosis and chronic obstructive lung disease, as well as chronic urinary tract infections in patients with permanent bladder catheter, and ventilator-associated pneumonia in intubated patients, and is also an important pathogen in chronic wounds. Antibiotic treatment cannot eradicate these biofilm infections due to their intrinsic antibiotic tolerance and the development of mutational antibiotic resistance. The tolerance of biofilms to antibiotics is multifactorial involving physical, physiological and genetic determinants, whereas the antibiotic resistance of bacteria in biofilms is caused by mutations and driven by the repeated exposure of the bacteria to high levels of antibiotics. In this review both the antimicrobial tolerance and the development of resistance to antibiotics in P. aeruginosa biofilms is discussed. Possible therapeutic approaches based on the understanding of the mechanisms involved in the tolerance and resistances of biofilms to antibiotics are also addressed.